Cost-effectiveness of malaria microscopy and rapid diagnostic tests versus presumptive diagnosis: implications for malaria control in Uganda - Batwala, Vicent; Magnussen, Pascal; Hansen, Kristian S; Nuwaha, Fred (BioMed Central Ltd, 2011)
Current Uganda National Malaria treatment guidelines recommend parasitological confirmation either by microscopy or rapid diagnostic test (RDT) before treatment with artemether-lumefantrine (AL). However, the cost-effectiveness of these strategies has not been assessed at rural operational primary care centers.
Cost-effectiveness of malaria microscopy and rapid diagnostic tests versus presumptive diagnosis.
Keywords: Malaria microscopy, rapid diagnostic, tests versus, diagnosis, malaria control